UJI EFEKTIVITAS ANTIBAKTERI EKSTRAK DAUN BELIMBING WULUH (AVERRHOA BILIMBI L) TERHADAP PERTUMBUHAN BAKTERI KLEBSIELLA PNEUMONIAE SECARA IN VITRO - FIRSTY DWI HIDAYATI SIRAIT; YENITA .; ANCE ROSLINA; ILHAM HARIAJI (JURNAL ILMIAH MAKSITEK, 2020)
Infection is the most common disease in Indonesia. Infection disesase are caused by microorganisms such as the Klebsiellapneumoniae. While in fact, many plants can be used as traditional medicine, one of those is the leaves of Cucumber tree(Averrhoa bilimbi L). This study aims to determine the inhibitory power of leaves of Cucumber tree (Averrhoa bilimbi L) ongrowth of Klebsiella pneumoniae in vitro. This study used an experimental method. The technique used to measureantibiotic activity is the method of disk diffusion and continued by Kruskal-Wallis test and Mann-Whitney test Leaves ofCucumber tree (Averrhoa bilimbi L) at concentrations of 40%, 60%, 80%, 100%, cefotaxime, and aquabidest shows no clearzone. Leaves of Cucumber tree (Averrhoa bilimbi L) does not have an inhibitory power against Klebsiella pneumoniae.